Korelasi Antara Puyang dan Masyarakat Dalam Tradisi Sedekah Dusun Di Desa Cambai Kota Prabumulih - Lili Annisah1; Amilda; Santosa (Tanjak: Sejarah dan Peradaban Islam, 2024)
This research is entitled "Correlation Between Puyang and Community in the Dusun Almsgiving Tradition in Cambai Village, Prabumulih City" relating to the bond of puyang as an identity that originates from the community. Puyang is believed to be the founding ancestor and shaper of a civilization for the lives of the people of South Sumatra in ancient times. The figure of the puyang continues to be believed in by society's primitive beliefs, namely animism as a belief in the spirits of ancestors which has become a tradition passed down from generation to generation in everyday life. The main issues in this research are: [1] What are the oral traditions that developed in the Cambai Village community regarding their origins? [2] What is the process of implementing the village alms tradition in Cambai Village? [3] What is the relationship between the puyang and the people of Cambai Village in carrying out the village alms tradition? This research method uses an ethnographic method, which is an approach to one of the qualitative research methods that focuses on the phenomenon of the correlation between Puyang and society in the Dusun Almsgiving Tradition in Cambai Village, Prabumulih City. The data sources used consist of: Primary data, namely direct observation in the field and conducting interviews. Meanwhile, secondary data includes books, journals, theses and articles. The data collection methods used by researchers are observation, interviews and documentation. Data analysis in this research uses analytical techniques, namely data collection, interpretation and writing of results which are carried out simultaneously. Based on the analysis of the research results and discussion, the researcher draws the conclusion that the Dusun Almsgiving Tradition has been carried out since ancient times by our ancestors and continues to be carried out from generation to generation until now, and the relationship between the puyang and the village community is established in this tradition.